Dispersion interactions between neighboring Bi atoms in (BiH3)2 and Te(BiR2)2. Issue 20 (13th March 2018) - Haack, Rebekka; Schulz, Stephan; Jansen, Georg
Abstract : Triggered by the observation of a short Bi⋯Bi distance and a BiTeBi bond angle of only 86.6° in the crystal structure of bis(diethylbismuthanyl)tellurane quantum chemical computations on interactions between neighboring Bi atoms in Te(BiR2 )2 molecules (R = H, Me, Et) and in (BiH3 )2 were undertaken. Bi⋯Bi distances atoms were found to significantly shorten upon inclusion of the d shells of the heavy metal atoms into the electron correlation treatment, and it was confirmed that interaction energies from spin component‐scaled second‐order Møller–Plesset theory (SCS‐MP2) agree well with coupled‐cluster singles and doubles theory including perturbative triples (CCSD(T)). Density functional theory‐based symmetry‐adapted perturbation theory (DFT‐SAPT) was used to study the anisotropy of the interplay of dispersion attraction and steric repulsion between the Bi atoms. Finally, geometries and relative stabilities of syn–syn and syn–anti conformers of Te(BiR2 )2 (R = H, Me, Et) and interconversion barriers between them were computed. © 2018 Wiley Periodicals, Inc. Abstract : Triggered by experimental observations of a short Bi⋯Bi distance and a very small BiTeBi bond angle in Te(BiEt2 )2 the interplay of dispersion attraction and steric repulsion between neighboring bismuth atoms is investigated through quantum chemical calculations of the (BiH3 )2 model system and of Te(BiR2 )2 molecules (R = H, Me, Et). Syn–syn and syn–anti conformers of Te(BiR2 )2 are found to be energetically close and to interconvert easily.